Legal Form and Earnings Properties. Issue 3 (2nd July 2016) - Bigus, Jochen; Georgiou, Nadine; Schorn, Philipp
Abstract: We investigate whether the financial accounting choices made by German private firms depend on legal form. Legal form determines dividend rights, liability status and the owners' obligations to run the business and, thus, influences agency problems of debt and equity. Consequently, we find that earnings properties depend on legal form. We expect, and find, that corporations exhibit higher levels of income smoothing and conservatism than partnerships and one-person businesses. Corporations are also more likely to disclose small profits. However, generally, there are no significant differences in earnings properties between one-person businesses and partnerships. The results are robust to different econometric specifications including endogeneity concerns (e.g. propensity score matching). Earnings properties of private firms seem to be driven to a considerable extent by agency problems of debt.